The Divine Perspestive(s): God and Time - Pailin, David A. (Theoria et Historia Scientiarum, 2007)
So far as the credibility of theism is concerned, it is important to clarify what is meant by God and time since this is basic to a proper appreciation of the relation of God to the processes of reality. Widespread and traditional thought about these matters has put forward certain notions that are at least debatable and probably incredible. In this paper, therefore, I want to consider what may emerge about the relationship between God and time if we understand.